O verbo se fez carne: a unidade teológico-retórico-política na oratória de Dom Aquino Corrêa - Lazzaretti, Jildonei (2018)
This study analyzes the oratory of Dom Aquino Corrêa, identifying in his discourses the existence of a “theological-rhetorical-political unity”, a category formulated by Alcir Pécora (1994) in his study on the sermons of priest Antônio Vieira. Initially, in order to verify the applicability of such a category to the discourses of Dom Aquino, an approach is developed between the two orators, recognizing similarities and distances. Posteriorly, the theological, rhetorical and political presuppositions that contribute to the constitution of such a unity are identified. Finally, during the analysis of Dom Aquino's discourses – which included texts from different periods of his life and different contexts of enunciation – it was found that such a theological-rhetorical-political unity has as its paradigm the mystery of the Incarnation of Christ, more specifically, its two natures, divine and human, which are associated, by analogy, with the Church and the State, which come to be seen, respectively, as “Mystical Body” and as “civic body”.